Challenges of Human Rights in Nepal - Kandel, Ishwori Prasad (KMC Research Journal, 2024)
Though human rights have been violated by different sectors in the name of war, movement, rule and security management, it is the fundamental rights for all the people across the globe. During the development process of human rights at an international level various declarations have been enacted. The Vienna Declaraton-1993 called on the United Nations (UN) member states for the establishment of independent and autonomous national human rights institutions. With the political change in 1989, the protection and promotion of human rights was accepted as the state policy, although the inception of the national human rights institution didn't turn out to be easy as it was anticipated. As a result, the National Human Rights Commission Act-1996 was enacted following the vibrant civil society movement by human rights workers, legal professionals, and media. Civil society, intellectual community and professional organizations demanded the establishment of the National Human Rights Institution. Even after four years of the enactment of the Act, the National Human Rights Commission could not be brought into existence. Taking a far more tightly structure approach, Great oberleitner sets out to explore the benefits and dangers of the institutionalization of human rights, and the impact this has on their development, implementation, enforcement, and promotion around the world. The constitution of Nepal has provisionalized the right to human right.